Civil Service Police Unit principle : no punishment and no taxation without representation - Sarip Sarip; Diana Fitriana; Absori Absori; Khudzaifah Dimyati; Harun Harun (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The present study aims to scrutinize the Indonesian Civil Service Police Unit (henceforth: Satuan Polisi Pamong Praja/CSPU) in enforcing local regulations. In enforcing the local regulations, the principle of “no punishment without representation” is applied to the formulation of criminal sanctions, while the principle of “no taxation without representation” is conducted to regional development funding. This study employs normative qualitative approach to obtain legal facts encountered by CSPU. The findings indicated that CSPU merely works as administrative officers with their insignificant roles. Furthermore, the contents of the criminal sanctions for regional development funding position it as an instrument to influence the perception of the regional communitydue to their lack of coordination in implementing the two principles. Furthermore, the CSPU is deemed to be restricted due to the absence of regulations that strengthen their duties to enforce the local regulations. Therefore, it can be inferred that the lack of support for legal products in enforcing local regulations is considered an obstacle for those CSPU to truly play their main role as investigators towards the violation of local regulations. Furthermore, the local government does not place more emphasis on the principles of criminal sanctions as well as the escorting of financial capital in regions.